2019
DOI: 10.1186/s12885-019-6386-6
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus drug-eluting beads chemoembolization for infiltrative hepatocellular carcinoma: a comparison of efficacy and safety

Abstract: BackgroundTo compare the efficacy and safety between conventional transarterial chemoembolization (cTACE) and drug-eluting beads TACE (DEB-TACE) in patients with infiltrative hepatocellular carcinoma (iHCC).MethodsA total of 89 iHCC patients who were treated with either cTACE (n = 33) or DEB-TACE (n = 56) between April 2013 and September 2017 were included in this retrospective study. Patients with the situations that might have a poor outcome were defined as advanced disease including Child-Pugh class B, bilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…In regard to probable explanations, we speculated that the result of total AEs incidence being the highest in cTACE group may be related to the technical process of cTACE, including the application of lipiodol and large size embolization particles, which could both contribute to a higher AEs incidence. 21 , 26 Furthermore, we also found a difference in incidence of fever, fatigue, and nausea among the three therapies, and to be specific, the incidences of fever, fatigue, and nausea were increased in cTACE group compared to RFA group, fever incidence was increased in DEB-TACE group in comparison to RFA group, and fatigue incidence was elevated in cTACE group compared to DEB-TACE group. These findings indicated that RFA was superior to cTACE and DEB-TACE in HCC patients regarding fever, fatigue, and nausea incidences, which could provide some information when it comes to decision-making in the management of HCC patients.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In regard to probable explanations, we speculated that the result of total AEs incidence being the highest in cTACE group may be related to the technical process of cTACE, including the application of lipiodol and large size embolization particles, which could both contribute to a higher AEs incidence. 21 , 26 Furthermore, we also found a difference in incidence of fever, fatigue, and nausea among the three therapies, and to be specific, the incidences of fever, fatigue, and nausea were increased in cTACE group compared to RFA group, fever incidence was increased in DEB-TACE group in comparison to RFA group, and fatigue incidence was elevated in cTACE group compared to DEB-TACE group. These findings indicated that RFA was superior to cTACE and DEB-TACE in HCC patients regarding fever, fatigue, and nausea incidences, which could provide some information when it comes to decision-making in the management of HCC patients.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, we also observed that cTACE was independently correlated with increased risk of total AEs, fatigue, and nausea/vomiting, this could result from the features of cTACE treatment involving the use of lipiodol and large size embolization particles, as explained previously. 21,26 Moreover, we also found that male gender, bronchial asthma, heart disease, diabetes mellitus, disease duration, blood supply of tumor, ablation history, TACE history, radioactive seeds implantation history, TBIL level, ALT level, and complete embolization/ablation were also independent predictive factors for total AEs or specific AEs. These probably could provide more information on the management of HCC patients regarding choosing the optimal therapy to maximize the elimination of AEs.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…If IPSO microdroplets are too small for the inner diameter of the tumor vasculature, they may pass through the tumor tissues and normal tissues; if the microdroplets are too large, they are trapped proximal to the tumor vasculature (15,16). Drug-eluting beads (DEBs) have been developed for transcatheter treatment of HCC because DEBs can deliver higher dose of the anticancer agents and prolong the contact time with the tumor (17)(18)(19)(20)(21). Treatment with DEBs reduces the amount of anticancer agent reaching the systemic circulation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Most HCC patients are typically diagnosed at intermediate or advanced stages when curative treatments cannot be applied [ 71 , 72 ]. According to the Barcelona Clinic Liver Cancer (BCLC) staging system [ 73 ] and several treatment guidelines [ 6 , 7 ], TACE is the gold standard for patients with intermediate-stage HCC.…”
Section: Methodsmentioning
confidence: 99%